A Wound Treatment Strategy for "Super Long-Term Difficult-to-Heal Wounds": A Single-Center Retrospective Study. (December 2022) - Ye, Chunjiang; Zhang, Yuanhai; Han, Chunmao; Mao, Shulei; Ni, Liangfang; Liu, Jia; Wu, Junmei; Zhang, Jianfen
Chronic wounds are a challenge for clinicians. Treating chronic wounds in elderly patients is difficult due to comorbidities and poor immunity, tissue renewal, and regeneration. This study shared the therapeutic experiences of 40 patients with super long-term difficult-to-heal wounds and to describe the effects of negative pressure wound therapy (NPWT)-assisted debridement and autologous scalp grafting. Elderly patients with chronic wounds for more than 60 years who underwent NPWT-assisted debridement and autologous scalp grafting between 2015 and 2017 were retrospectively analyzed. Forty patients were identified and analyzed. Among all patients, the average wound area was 56 (interquartile range 30-90) cm 2 . The wound infection rate was 82.1%, and that before the first autologous scalp grafting was 51.3%. The average total number of surgeries was 3, and the number of times the NPWT device was replaced was once. A total of 97.4% of patients had one autologous scalp grafting performed. The transplanted scalp survived completely in 97.4% of patients. One hundred percent of patients had no postoperative complications and healed. The average wound healing time was 34.5 ± 10.1 days. This study showed that NPWT-assisted debridement and autologous scalp grafting have the advantages of high survival rate of the skin and decreased wound recurrence and may be a suitable treatment for super long-term difficult-to-heal wounds in elderly patients.